Correlation between intermolecular hydrogen bonds and melting points of uranyl nitrate complexes with cyclic urea derivatives. (16th August 2015) - Suzuki, Tomoya; Takao, Koichiro; Kawasaki, Takeshi; Harada, Masayuki; Nogami, Masanobu; Ikeda, Yasuhisa
Graphical abstract: We have determined crystal structures of UO2 (NO3 )2 (0a )2 (0a : 2-imidazolidone), UO2 (NO3 )2 (0b )2 (0b : tetrahydro-2-pyrimidone) and UO2 (NO3 )2 (1a )2 (1a : 1-methyl-2-imidazolidone) by using single crystal X-ray analysis, and examined correlations between melting points (mps) and intermolecular hydrogen bonds (HBs) of UO2 (NO3 )2 (CU)2 (CU: cyclic urea derivatives) and UO2 (NO3 )2 (NRP)2 (NRP: pyrrolidone derivative). Abstract: To clarify requirements for forming UO2 (NO3 )2 (CU)2 (CU: cyclic urea derivative) and UO2 (NO3 )2 (NRP)2 (NRP: N -alkylated pyrrolidone derivative) with high melting points (mps), molecular and crystal structures of UO2 (NO3 )2 (0a )2 (0a : 2-imidazolidone), UO2 (NO3 )2 (0b )2 (0b : tetrahydro-2-pyrimidone) and UO2 (NO3 )2 (1a )2 (1a : 1-methyl-2-imidazolidone) were determined by means of single crystal X-ray analysis. Melting points (mps) of these complexes were compared with each other and those of other UO2 (NO3 )2 (CU)2 and UO2 (NO3 )2 (NRP)2 . As a result, the uranyl nitrate complexes with0a, 0b and1a exhibit typical structural properties of UO2 (NO3 )2 L2 (L: unidentate ligand); i.e., hexagonal bipyramidal coordination geometry, and two bidentate NO3 − and two CUs located at trans positions in an equatorial plane of UO2 2+ ion. Several intermolecular N–H⋯O hydrogen bonds (HBs) were found in the crystal structures of UO2 (NO3 )2 (0a )2, UO2 (NO3 )2 (0b )2 and UO2 (NO3 )2 (1a )2 . In contrast, no intermolecular C–H⋯O HBs were formed in these crystal structures. The intermolecular HBs were discussed in connection with mps of UO2 (NO3 )2 (CU)2 and UO2 (NO3 )2 (NRP)2 including those reported previously. The mp tends to increase as the number of N–H⋯O HBs per molecule increases, whereas effects of C–H⋯O HBs on the mps is not very significant. These results suggest that the intermolecular N–H⋯O HBs strongly contribute to form a uranyl nitrate complex with high mps.